CLINICAL LABORATORY ROLE IN BIOCHEMICAL ANALYSIS FOR EARLY DETECTION OF METABOLIC DISORDERS - Erkinova Maxfirat,; Nurmatova M.A., (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article examines the role of clinical laboratories in the biochemical analysis of blood and body fluids for the early detection of metabolic disorders. Key biochemical parameters, common laboratory tests, and modern analytical techniques are discussed. The importance of early diagnosis and continuous monitoring in improving patient outcomes is emphasized.